Triggering Role of Trauma on Initiation of SAPHO Syndrome: A Case Report - Ümit Dinçer; Barış Nacır; Engin Çakar; Mehmet Zeki Kıralp; Hasan Dursun (Archives of Rheumatology, 2008)
SAPHO is a clinical syndrome characterized by Synovitis, Acne, Pustulosis, Hyperostosis, and Osteitis. Since the time it was first described, it has been diagnosed at an ever increasing rate. Although cases associated with palmoplantar pustulosis (PPP) have been reported, the relationship of the SAPHO syndrome and spondyloarthropathies with trauma remains poorly understood. While there are case reports in the literature which describe spondyloarthropathies following physical trauma, information exists indicating that psychological trauma and stress can also trigger or exacerbate palmoplantar pustulosis and psoriasis. Our case had PPP which arose 3 months after experiencing trauma on her shoulder and neck regions. In addition, she had low back pain and anterior chest wall pain which appeared after a short time following the onset of PPP. Unilateral sacroiliitis and bilateral sternoclavicular joint involvement were established in the patient. (Romatizma 2008; 23: 106-8)